Healthcare professionals' perceptions and management of obesity & knowledge of glucagon, GLP‐1, GIP receptor agonists, and dual agonists - W. Timothy Garvey; Cathy D. Mahle; Trevor Bell; Robert F. Kushner (Obesity Science & Practice, 2024)
Abstract Background Anti‐obesity medications (AOMs) have historically had limited weight‐loss efficacy. However, newer glucagon‐like peptide‐1 receptor agonist (GLP‐1 RA)–based therapies seem to be more effective, including dual agonists of GLP‐1R and the glucagon receptor (GCGR) or glucose‐dependent insulinotropic polypeptide receptor. Objective To explore healthcare professionals' (HCPs) experience in obesity treatment and their understanding of agonists of GCGR, glucose‐dependent insulinotropic polypeptide (GIP) RA, and GLP‐1 RA. Methods This cross‐sectional online survey of HCPs prescribing AOMs was conducted in the United States in 2023 with a questionnaire designed to evaluate prescribing behavior and understanding of GCGR, GIP RA, and GLP‐1 RA. Results The 785 respondents (251 primary‐care physicians [PCPs], 263 endocrinologists, and 271 advanced practice providers [APPs]) reported 55% of their patients had obesity (body mass index ≥30 kg/m2 or ≥27 with weight‐related complications) and recommended AOMs to 49% overall, significantly more endocrinologists (57% of patients, p < 0.0005) than PCPs (43%) or APPs (46%). The greatest barriers to treatment were medication cost/lack of insurance (mean 4.2 on 1–5 scale [no barrier–extreme barrier]), low patient engagement/adherence (3.3), and inadequate time/staff (3.1). Metformin was the type 2 diabetes (T2D) medication most commonly prescribed to treat obesity in T2D patients (92.5% of respondents). Most HCPs (65%) were very/extremely familiar with GLP‐1 RA, but only 30% with GIP RA and 16% with GCGR. Most HCPs expected dual GCGR/GLP‐1 RA to benefit many obesity‐related conditions; however, only a minority of HCPs perceived that they would benefit non‐cardiometabolic complications of obesity. Conclusions Among HCPs prescribing AOMs, gaps exist in the management of people living with obesity as <50% are prescribed AOMs. Barriers to treatment indicate a need to improve access to AOMs. HCPs were less familiar with GCGR or GIP RA than GLP‐1 RA but expect dual GCGR/GLP‐1 RA may offer additional benefits, potentially addressing treatment barriers and access. Thus, there is a need for greater education among HCPs regarding the mechanism of action and therapeutic effects of GCGR agonists, and dual GCGR/GLP‐1 RA, so that the full range of obesity‐related complications can be effectively treated.